Cybersecurity blue team strategies : uncover the secrets of blue teams to combat cyber threats in your organization - Sehgal, Kunal; Thymianis, Nikolaos (Packt Publishing, Limited, 2023)
This book will help you understand how a blue team is formed and why it is crucial for businesses. You'll learn different security controls, such as preventive and defensive controls, and become equipped to set up a blue team from scratch.